The Influence Of Digital Marketing, Customer Trust And Brand Image On Customer Satisfaction At Mcdonald's Fast Food Restaurant In Cilegon City - Muhamad Suhaemi; Nabila Zahra Auliya; Dhanny Isnaeni Darmawan; Yoga Adiyanto (University of Science and Computer Technology, 2023)
. This study aims to analyze the effect of digital marketing on brand image, trust and consumer satisfaction at McDonald's fast food restaurants in Cilegon City.The sampling technique in this study was purposive sampling, namely the sample selection method based on certain criteria. That is, McDonald's consumers who have bought McDonald's at least once. Based on the results of the study it can be concluded that: There is a positive and significant influence between Digital marketing on Consumer Satisfaction at Mcdonald's Fast Food Restaurants in Cilegon City, There is a positive and significant influence between Customer Trust on Customer Satisfaction at Mcdonald's Fast Food Restaurants in Cilegon City, There is a positive and significant influence between Brand Image on Customer Satisfaction at Mcdonald's Fast Food Restaurants in Cilegon City, There is a positive and significant influence between Digital marketing, Consumer Trust and Brand Image on Consumer Satisfaction at Mcdonald's Fast Food Restaurants in Cilegon City.